Homodimerization of the human U1 snRNP-specific protein C. - Gunnewiek, J M (1995)
The U1 snRNP-specific protein C contains an N-terminal zinc finger-like CH motif which is required for the binding of the U1C protein to the U1 snRNP particle. Recently a similar motif was reported to be essential for in vivo homodimerization of the yeast splicing factor PRP9. In the present study we demonstrate that the human U1C protein is able to form homodimers as well. U1C homodimers are found when (i) the human U1C protein is expressed in Escherichia coli, (ii) immunoprecipitations with anti-U1C antibodies are performed on in vitro translated U1C, and when (iii) the yeast two hybrid system is used. Analyses of mutant U1C proteins in an in vitro dimerization assay and the yeast two hybrid system revealed that amino acids within the CH motif, i.e. between positions 22 and 30, are required for homodimerization.